Immunohistochemical study of acinic cell carcinoma of minor salivary gland - Crivelini, Marcelo Macedo [UNESP]; deSousa, SOM; deAraujo, V. C. (Elsevier B.V., 1997)
Acinic cell carcinoma (ACC) is a rare salivary gland tumour, making up 4% of all minor salivary gland tumours. Typically, it is composed of acinic cells although transitional and duct-like cells are also identified. In the present study, a panel of antibodies was applied to eight minor salivary gland ACCs. Antibodies tested were: cytokeratins 7, 8, 13, 14, 18, 19, vimentin and actin (HHF35). Immunohistochemical staining revealed that cytokeratin 8, among the tested antibodies, was the more specific to neoplastic cells with a pattern of distribution quite variable and peculiar. This staining may be useful in the recognition of neoplastic acinic cells. (C) 1997 Elsevier B.V. Ltd.
Keywords: salivary gland neoplasm; salivary gland minor; salivary gland; immunohistochemistry